Analysis of Charismatic Leadership Characteristics of Students in Elementary School : Analisis Karakteristik Kepemimpinan Karismatik Siswa Di Sekolah Dasar - Muhammad Reksa Samudera; Supriyadi Supriyadi (Academia Open, 2022)
The formation of leadership character is a series of ideas that are concreted in the form of programs or activities to form the leadership character that exists in the object (students), so it is hoped that the charismatic leadership character can stick strongly and be explained in everyday life. In the world of education, leadership elementary schools are felt to help students as the nation's next generation to be ready to become world leaders with noble character, so it is very important to develop leadership characters from an early age. This research method uses qualitative research. Data were collected by means of interviews, observations, and documentation studies. From this research, it can be concluded that the formation of leadership character in SD Lab School Muhammadiyah 1 Candi is carried out through teaching and learning activities. The formation of charismatic leadership characters at SD Lab School Muhammadiyah 1 Candi also has supporting factors and inhibiting factors. And also SD Lab School Muhammadiyah 1 Candi has various efforts to overcome obstacles in the formation of characteristics in students.